PENGKAJIAN BEBERAPA TANAMAN EMPON - EMPON DI DESA BALESARI KECAMATAN WINDUSARI KABUPATEN MAGELANG - Siti Nurul Iftitah; Gembong Haryono (JURNAL VIGOR, 2018)
The need of empon-empon plants increases also with the public awareness of health and the usage of herbal ingredients as remedies. The type of plant empon-empon in Indonesia is various and each of them has certain purpose which can be used as herbal medicine / traditional herbal medicine. Empon-empon plants can be planted monoculture on open land or planted with tumpangsari method under annual crops / agroforestry. This research is aimed to find out the existing empon-empon plant, to understand the way of cultivating empon-empon and to motivate farmers plant the empon-empon based on Good Agriculture Practices (GAP), so they can produce high quality of empon-empon, in order to be accepted in the herbal medicine industry. The research was conducted by descriptive method by inventorying, identifying and reviewing some of the existing empon-empon plants. Observations were made on 25 farmer samples divided into 5 villages. The results showed that the majority of Balesari villagers know and have empon-empon plants, such as ginger, turmeric ,and galangal which is grown in the moor without maintenance based on GAP. There has been no processing of empon-empon crops until now, so a training on empon-empon plant processing is required in order to increase the farmer income.